Evidence-Based CompensACTION: Unlocking climate finance for smallholders - Costa Junior, Ciniro; Dittmer, Kyle M.; Ezzine De-Blas, Driss; Blundo, Genowefa (2025)
This document presents the initial outputs of the Alliance’s research, including a systematic review of global experiences, the identification of key barriers such as high transaction costs and weak policy integration, and early insights into innovative models that can make PES more scalable and inclusive. By bringing science into the design of financial mechanisms, the Alliance supports CompensACTION in building pathways that improve farmer incomes sustainably, ensuring benefits are measurable, accessible to smallholders, and resilient to market and policy shifts. These insights are already informing pilots with IFAD, KfW-Incofin and the World Bank, guiding investment strategies and contributing to robust and feasible models. Ultimately, this work provides the evidence base for scaling opportunities and farmer engagement, laying the foundation for a new generation of PES schemes that are inclusive, scalable, and sustainable.